2001
DOI: 10.1042/bj3570373
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor of the parasitic nematode Trichinella spiralis

Abstract: cDNAs were obtained for macrophage migration-inhibitory factor (MIF)/l-dopachrome methyl ester tautomerase homologues from the parasitic nematodes Trichinella spiralis (TsMIF) and Trichuris trichiura (TtMIF). The translated sequences, which were partly confirmed by sequencing of proteolytic fragments, show 42 and 44% identity respectively with human or mouse MIF, and are shorter by one C-terminal residue. Unlike vertebrate MIF and MIF homologues of filarial nematodes, neither TsMIF nor TtMIF contain cysteine r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…In another experiment performed with T. britovi (15000 larvae) on pigs, CPK, AST and ALT presented increased activity during the infection (Oltean et al, 2009). The irrelevant results obtained in the phagocytic assay could be explained through the results obtained by Pennock et al (1998), Tan et al (2001) and Freitas and Pearce (2010), who demonstrated the presence of a macrophage migration-inhibitory factor (MIF) in T. spiralis larvae, very similar to a mammalian cytokine, which might contribute to subversion of host defences. The mammalian MIF is inhibitory for monocyte-macrophage migration, towards glucocorticoid activity (Calandra et al, 1995), immunoglobulin synthesis (Tomura et al, 1999) and natural killer-cell activity (Apte et al, 1998), but not all this properties have been demonstrated yet in MIF produced by T. spiralis.…”
Section: Discussionmentioning
confidence: 84%
“…In another experiment performed with T. britovi (15000 larvae) on pigs, CPK, AST and ALT presented increased activity during the infection (Oltean et al, 2009). The irrelevant results obtained in the phagocytic assay could be explained through the results obtained by Pennock et al (1998), Tan et al (2001) and Freitas and Pearce (2010), who demonstrated the presence of a macrophage migration-inhibitory factor (MIF) in T. spiralis larvae, very similar to a mammalian cytokine, which might contribute to subversion of host defences. The mammalian MIF is inhibitory for monocyte-macrophage migration, towards glucocorticoid activity (Calandra et al, 1995), immunoglobulin synthesis (Tomura et al, 1999) and natural killer-cell activity (Apte et al, 1998), but not all this properties have been demonstrated yet in MIF produced by T. spiralis.…”
Section: Discussionmentioning
confidence: 84%
“…In clade I, the order Trichinellida contains the families Trichinellidae and Trichuridae, which contain the genera Trichinella and Trichuris, respectively. Trichinella spiralis secretes a mimic of macrophage migration inhibitory factor [85].…”
Section: Immunomodulationmentioning
confidence: 99%
“…This effect was confirmed via neutralizing anti-MIF antibodies which restored the migration of cells. Similarly to Bm-MIF, recombinant T. spiralis MIF (TsMIF) inhibited the migration of human peripheral blood mononuclear cells (PBMCs) [70].…”
Section: Nmifs and The Immune System Of The Hostmentioning
confidence: 99%